Wharton’s jelly mesenchymal stem cells: a concise review of their secretome and prospective clinical applications - Drobiova, Hana; Sindhu, Sardar; Ahmad, Rasheed; Haddad, Dania; Al-Mulla, Fahd; Al Madhoun, Ashraf (Frontiers in Cell and Developmental Biology, 2023)
Accumulating evidence indicates that most primary Wharton's jelly mesenchymal stem cells (WJ-MSCs) therapeutic potential is due to their paracrine activity, i.e., their ability to modulate their microenvironment by releasing bioactive molecules and /factors collectively known as secretome. These bioactive molecules and/ factors can either be released directly into the surrounding microenvironment or can be embedded within the membrane-bound extracellular bioactive nano-sized (usually 30-150 nm) messenger particles or vesicles of endosomal origin with specific route of biogenesis, known as the exosomes or carried by relatively larger particles (100 nm-1 μm) formed by outward blebbing of plasma membrane called microvesicles (MVs); exosomes and MVs are collectively known as extracellular vesicles (EVs). These bioactive molecules and/ factors found in secretome are of various types, including cytokines, chemokines, cytoskeletal proteins, integrins, growth factors, angiogenic mediators, hormones, metabolites, 2 This is a provisional file, not the final typeset article and regulatory nucleic acid molecules. As expected, the secretome performs different biological functions, such as immunomodulation, tissue replenishment, cellular homeostasis, besides possessing anti-inflammatory and anti-fibrotic effects. This review highlights the current advances in research on the WJ-MSCs' secretome /exosome and its prospective clinical applications.